2020
DOI: 10.1177/1049909120976398
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Death on Hospitalization in Patients With Advanced Cancer in Palliative Care

Abstract: Background: Prognostic assessment is essential to plan the care of patients with advanced cancer in palliative care. Objective: Thus, this study aims to assess the predictors of death in inpatients with advanced cancer in palliative care. Methods: This is a clinical, observational cohort study with patients aged >20 years, of both genders, evaluated within 48 hours of the first hospitalization. The independent variables were tumor location, nutritional risk [through the Patient-Generated Subjective Global A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
3
2
Order By: Relevance
“…The prevalence of malnutrition by the PG-SGA was 97.92%, and was above 90% in all participating units. Our result was higher than the 79.39% value found in 23 904 patients with common malignant tumors by Song et al41 In other, smaller sample size studies, the malnutrition rate was 43.3% in patients with cancer before radiation therapy,42 94.2% in patients with advanced cancer,43 and 83.6%44 and 75.9%43 in a palliative care unit. In our hospital, oncology patients were at different disease phases, but the nutritional status evaluated by the PG-SGA was based upon their assessment of nutritional risk, which contributed to the higher malnutrition rate.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The prevalence of malnutrition by the PG-SGA was 97.92%, and was above 90% in all participating units. Our result was higher than the 79.39% value found in 23 904 patients with common malignant tumors by Song et al41 In other, smaller sample size studies, the malnutrition rate was 43.3% in patients with cancer before radiation therapy,42 94.2% in patients with advanced cancer,43 and 83.6%44 and 75.9%43 in a palliative care unit. In our hospital, oncology patients were at different disease phases, but the nutritional status evaluated by the PG-SGA was based upon their assessment of nutritional risk, which contributed to the higher malnutrition rate.…”
Section: Discussioncontrasting
confidence: 73%
“…38 In our study, the prevalence of mal-nutrition by the SGA was 47.34%, which was similar to findings (48.1%) reported by Waitzberg et al, 39 but higher than the values (27.4%) reported by Pirlich et al 40 In our study, patients in the MICU, hematology, and respiratory medicine units showed a higher rate of malnutrition (above 85%), and patients in gastroenterology surgical wards showed a slightly lower malnutrition rate, which was also reported by Pirlich et al 40 The prevalence of malnutrition by the PG-SGA was 97.92%, and was above 90% in all participating units. Our result was higher than the 79.39% value found in 23 904 patients with common malignant tumors by Song et al 41 In other, smaller sample size studies, the malnutrition rate was 43.3% in patients with cancer before radiation therapy, 42 94.2% in patients with advanced cancer, 43 and 83.6% 44 and 75.9% 43 in a palliative care unit. In our hospital, oncology patients were at different disease phases, but the nutritional status evaluated by the PG-SGA was based upon their assessment of nutritional risk, which contributed to the higher malnutrition rate.…”
Section: Discussioncontrasting
confidence: 70%
“…The median survival times were: KPS 80 to 100 = 215 days; KPS 60 to 70 = 119 days; KPS 40 to 50 = 49 days; and KPS 10 to 30 = 29 days. According to Rosa et al 14 based on patient data from the same institution, KPS was a strong prognostic factor for reduced survival in hospitalized patients, with KPS 30-40% being associated with worse survival. In this context, this work adds evidence that the KPS value for each primary tumor site may represent a different prognosis in the last month of life.…”
Section: Discussionmentioning
confidence: 99%
“…This was expected, considering that KPS and ECOG-PS are recognized as important scales for decision-making in cancer care and have good predictive accuracy for survival. (37)(38)(39)(40) Therefore, even though nutritional risk preceded COVID-19 diagnosis, its predictive accuracy was similar to that of the performance status scales and other prognostic tools, such as the Palliative Prognostic Score (C-statistic: >0.79), the Palliative Prognostic Index (C-statistic: >0.75), (41) the Alternative International Prognostic Score-E (C-statistic: 0.70), (42) and the American Joint Committee on Cancer TNM Classification of Malignant Tumors (C-statistic: 0.74). (43) Published evidence about nutritional risk in patients with cancer and COVID-19 remains scant; however, a strong association has been found between lower survival and nutritional risk among non-cancer patients with COVID-19.…”
Section: ❚ Discussionmentioning
confidence: 99%